Using technology and e-learning maximise learning experience impact - UMP, PNC (2020)
Lecturers of Universiti Malaysia Pahang (UMP) activated virtual classroom (e‐learning) for all teaching and learning activities on 17 March 2020. The switch was due to the announcement through the Administrative Circular No. 3/2020 issued by the university to tackle the spread of Covid‐19.